Hukum Potong Tangan Dalam Qs. Al-Maidah Ayat 38 : (Studi Penafsiran Perspektif Hermeneutika Nasr Hamid Abu Zayd) - Annisa Nuril Hakim, Gayuh; Munawir, Munawir (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
Interpretation of the Qur'an in the context of legal cases, especially the law of cutting hands, often gives rise to different interpretations. This paper discusses the interpretation of the law of cutting hands for the perpetrators of theft in QS. Al-Maidah verse 38. This research needs to be carried out because the authors have not found the firmness of the hand amputation punishment for the perpetrators of theft in the current context. The researcher will examine this verse with a hermeneutic approach. One of the interesting hermeneutic theories to be studied in this paper is Nasr Hamid Abu Zayd's hermeneutics, which offers a contextual reading. Abu Zayd's hermeneutics consists of three main pillars, namely determining meaning (dalalah), exploring significance (maghza) and finding maskut 'anhu (unspeakable dimensions). Based on the application of the hermeneutics, it is found that the meaning (dalalah) of QS. Al-Maidah verse 38 the punishment for the perpetrators of theft is the punishment of cutting off the hands, while the significance (maghza) of the verse namely the punishment of cutting off the hands intends to provide a deterrent effect for the perpetrators of theft so that the theft will not be repeated. As for the maskut 'anhu (unspeakable dimension) of the verse, namely the punishment of cutting off hands can be replaced with other punishments that are relevant to the context of today's times, which still provide a deterrent effect, namely the heaviest fines or imprisonment for a long period of time. This research is a qualitative study with the type of literature (library search) with the primary source QS. Al-Maidah verse 38 and secondary sources in the form of relevant articles, journals and literature.